Hubungan Obesitas Terhadap Kualitas Hidup Remaja Di SMA Santo Paulus Pontianak - Ramadhaniyati, Ramadhaniyati; Kawuryan, Uji; Sundaria, Bonifasia Ermiyati (Sekolah Tinggi Ilmu Keperawatan Muhammadiyah Pontianak, 2015)
Obesity is a condition that occurs as a result of food consumption that far exceeds demand. Obesity in  Indonesia  continues  to  increase both  in  urban  and  rural  areas  .  Obesity can increase the risk of morbidity and mortality and causes of delay in physical function and psychological  impact  on  the  quality  hidup.Tujuan  study  is  to  examine the relationship between obesity and quality of life of adolescents . This study used a cross sectional design. The sample was all over St. Paul high school students who meet the criteria Pontianak, to get the data obesity anthropometric measurements of height and weight . Quality of life data were collected through questionnaires . Univarian data analysis using frequency distribution, bivarian using independent t test . Then from the results of the data processing can determine the  relationship  between  adolescent  obesity  on  quality  of  life  in  St.  Paul  high  school Pontianak.